Disney frozen - Grupczynski, Kelly (London phoenix international publications, 2020)
There are many things to explore in seven scenes inspired by the Disney Frozen film. With the help of their parents they can search, point, and match, make comparisons and discover concepts such as rhyming, shapes, and counting
Linguistic notions
Keywords: Language and Languages